Nonlinear Degenerate Anisotropic Elliptic Equations with Variable Exponents and L1 Data (Journal of Partial Differential Equations, 2020)
"This paper is devoted to the study of a nonlinear anisotropic elliptic equation with degenerate coercivity, lower order term and $L^1$ datum in appropriate anisotropic variable exponents Sobolev spaces. We obtain the existence of distributional solutions."
Keywords: Sobolev spaces with variable exponents; anisotropic equations; elliptic equations; $L^1$ data.